Partial tax coordination in a repeated game setting - Jun-ichi Itaya; Makoto Okamura; Chikara Yamaguchi (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper addresses the problem of partial tax coordination among regional or national sovereign governments in a repeated game setting. We show that partial tax coordination is more likely to prevail if the number of regions in a coalition subgroup is smaller and the number of existing regions in the entire economy is larger. We also show that under linear utility, partial tax coordination is more likely to prevail if the preference for a local public good is stronger. The main driving force for these results is the response of the intensity of tax competition. The increased (decreased) intensity of tax competition makes partial tax coordination more (less) sustainable.
Keywords: H71; H77; 330; partial tax coordination; repeated game; tax competition; Steuerwettbewerb; Steuerpolitik; Internationale wirtschaftspolitische Koordination; Wiederholte Spiele; Koalition; Theorie